Mucosal acidification increases hydrogen sulfide release through up-regulating gene and protein expressions of cystathionine gamma-lyase in the rat gastric mucosa - Seyyed Ali Mard; Ali Veisi; Akram Ahangarpour; Mohammad Kazem Gharib-Naseri (Iranian Journal of Basic Medical Sciences, 2016)
Objective(s): This study was performed to investigate the effects of mucosal acidification on mRNA expression and protein synthesis of cystathionine gamma lyase (CSE), cystathionine beta synthase (CBS), and mucosal release of H2S in gastric mucosa in rats. Materials and Methods:Thirty-two rats were randomly assigned into 4 groups (8 in each), including: the control group, HCl (10 mM) treated group, HCl (100 mM) treated group, and one group to study the effect of Nω-Nitro-L-arginine methyl ester hydrochloride (L-NAME). Anesthetized rats underwent tracheostomy and midline laparotomy. Ninety min after the instillation of neutral or acidic solutions, animals were sacrificed and the gastric mucosa was collected to measure the H2S concentration by ELISA method and to quantify mRNA expression of CSE and CBS by quantitative real-time PCR (qRT-PCR). Protein synthesis was also detected by Western blot method. Results:Mucosal acidification with 10 and 100 HCl, significantly increased mucosal levels of H2S (P